The plants of Doñana national park’s marisma (Spain): a key element for conservation of an emblematic european wetland - García-Murillo, Pablo (Universidad Autónoma de Tamaulipas, 2014)
Doñana National Park (SW Spain) is the flagship of the Spanish State Protected Natural Areas. It includes one of the largest wetlands in Western Europe, the marsh, which also happens to be the largest sanctuary for migratory birds on the continent. The trophic and structural support for this wetland depends on the plant communities developed there. However, despite its importance, the level of knowledge about the marsh´s plants and their communities is limited. Here we present a Floristic Catalogue from the marsh encompassing 247 different taxa within 61 families. The biogeographic pattern of the marsh is atypical compared to other Mediterranean habitat. We find limited endemism and a predominance of species with large geographic ranges. We also describe the main plant communities from the marsh, which are organized according to time of flooding and soil salt concentration. We use this information to identify several problems that affect the conservation of ecosystems from Doñana National Park.